A Re-evaluation of the Anatomy of the Claustrum in Rodents and Primates—Analyzing the Effect of Pallial Expansion - Binks, Daniel; Watson, Charles; Puelles, Luis (Frontiers in Neuroanatomy, 2019)
The components of the claustrum have been identified by gene expression in mice, but there is still uncertainty about the location of homologous components in primates. To aid interpretation of homologous elements between rodents and primates, we used a current understanding of pallial topology, species-specific telencephalic deformation, and gene expression data. In both rodents and primates, pallial areas maintain conserved topological relationships regardless of relative differences in pallial expansion. The components of the claustrum in primates can, therefore, be identified on the basis of their conserved topological relationships and patterns of gene expression. In rodents, a fairly straight telencephalic long axis runs between the early septopreoptic and amygdalar poles of the pallium. In primates, however, the remarkable dorsal pallial expansion causes this axis to be distorted to form a C shape. This has resulted in a number of errors in the interpretation of the location of claustral components. These errors are likely to have resulted from the unexpected topographical positioning of claustral components due to the bent telencephalic axis. We argue that, once the telencephalic distortion has been accounted for, both rodents and primates have homologous claustral components, and that the topological relationships of these components are conserved regardless of differences in the relative expansion of pallial areas.